The Effectiveness of Self-regulated Couple Therapy on Intimacy and Marital Adjustment of Couples with Marital Problems - Tarkeshdooz, Zeynab; Jenaabadi, Hossein; Kord Tamini, Bahman (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:A marital relationship forms the family, and its continuity and survival depend on the marital relationship's continuation and survival. This study aimed to investigate the effectiveness of Self-regulated couple therapy on intimacy and marital adjustment of couples with marital problems. Materials and Methods:The present study was an applied and quasi-experimental design with pretest-posttest and follow-up with a control group. The statistical population of this study was all couples referred to counseling clinics in 2020. The sample consisted of 30 couples referred to counseling clinics in district 1 of Tehran, selected by convenience sampling method. The data were collected through the marital intimacy scale and marital adjustment questionnaire. Data were analyzed by repeated measure analysis of variance and SPSS.22 software. Results:The results showed that self-regulated couple therapy was effective in increasing intimacy (P<0.001) and marital adjustment (P<0.001) of couples with marital problems. Conclusion:Considering that self-regulated couple therapy promotes husband-wife relationships, as a result, its training improves couple relationships and consequently brings adjustment to couples. The couple's communication program has helped incompatible couples to continue their marital relationships again and increase their problem-solving skills to work on their problems in a constructive way.